The Colombian Strain of Trypanosoma cruzi Induces a Proinflammatory Profile, Neuronal Death, and Collagen Deposition in the Intestine of C57BL/6 Mice Both during the Acute and Early Chronic Phase - José Rodrigues do Carmo Neto; Arthur Wilson Florêncio da Costa; Yarlla Loyane Lira Braga; Fernanda Hélia Lucio; Ana Luisa Monteiro dos Santos Martins; Marlene Antônia dos Reis; Flávia Aparecida de Oliveira; Mara Rúbia Nunes Celes; Marcos Vinicius da Silva; Milton Adriano Pelli Oliveira; Juliana Reis Machado (Mediators of Inflammation)
The objective of this study was to evaluate the histopathological changes caused by infection with the Colombian strain of Trypanosoma cruzi (T. cruzi) in the acute and chronic experimental phases. C57Bl/6 mice were infected with 1000 trypomastigote forms of the Colombian strain of T. cruzi. After 30 days (acute phase) and 90 days (early chronic phase) of infection, the animals were euthanized, and the colon was collected and divided into two parts: proximal and distal. The distal portion was used for histopathological analysis, whereas the proximal portion was used for quantification of pro- and anti-inflammatory cytokines. In addition, the weight of the animals and parasitemia were assessed. The infection induced gradual weight loss in the animals. In addition, the infection induced an increase in interferon gamma (IFNγ) and tumor necrosis factor-alpha (TNF-α) in the intestine in the acute phase, in which this increase continued until the early chronic phase. The same was observed in relation to the presence of intestinal inflammatory infiltrates. In relation to interleukin (IL)-10, there was an increase only in the early chronic phase. The Colombian strain infection was also able to induce neuronal loss in the myenteric plexus and deposition of the collagen fibers during the acute phase. The Colombian strain of T. cruzi is capable of causing histopathological changes in the intestine of infected mice, especially in inducing neuronal destructions. Thus, this strain can also be used to study the intestinal form of Chagas disease in experimental models.